Simple Method to Calculate the Oscillating Lift on a Circular Cylinder in Potential Flow - Harijono Djojodihardjo (Journal of Mathematical and Fundamental Sciences, 1973)
Abstract. A simple potential flow model is presented to calculate the oscillating lift on a circular cylinder. In essence, the time dependent lift acting on a cylinder is due to the presence of a vortex shed off the separation point on the cylinder. The vortex strength and its trajectory is predicted employing the condition of zero force on the vortex and its feeding vortex sheet. The vortex breaks away from the cylinder and is convected by the fluid after the vortex strength reaches a maximum value, and another vortex is shed at the other side of the cylinder. Oscillating lift with the right order of magnitude of available experimental results was predicted. For subcritical flow, good agreement is obtained between the predicted Strouhal number and that found experimentally.  Ringkasan. Suatu model aliran potensial sederhana diuraikan untuk menghitung gaya angkat yang berosilasi pada silinder lingkaran. Pada dasarnya, gaya angkat yang berosilasi ini disebabkan karena adanya vortex yang dilepaskan oleh silinder dari titik pemisahan. Kekuatan vortex dan lintasannya dihitung dengan menggunakan syarat bahwa gaya pada vortex dan bidang vortex yang menumbuhkannya harus sama dengan nol. Vortex ini terputus dari silinder pada waktu kekuatannya mencapai maksimum, dan vortex yang lain mulai dilepaskan pada sisi silinder yang lain. Hasil perhitungan menunjukkan harga gaya angkat maksimum yang mendekati harga yang diperoleh secara eksperimentil. Demikian pula, untuk aliran subkritis, diperoleh hasil perhitungan bilangan Strouhal yang mendekati harga yang diperoleh secara eksperimen.